Totally minimally invasive radical gastrectomy with the da Vinci Xi® robotic system versus straight laparoscopy for gastric adenocarcinoma. Issue 6 (2nd September 2020) - Aktas, Aydin; Aytac, Erman; Bas, Mustafa; Gunes, Orgun; Tarcan, Serim Hande; Esen, Eren; Gokler, Cihan; Aghayeva, Afag; Uylas, Ufuk; Ozben, Volkan; Zengin, Akile; Sumer, Fatih; et al.
Abstract: Background: Data regarding the outcomes of pure minimally invasive techniques of radical gastrectomy are scarce. We aimed to compare short‐term post‐operative outcomes in patients undergoing totally minimally invasive radical gastrectomy with the da Vinci Xi ® robotic system versus straight laparoscopy for gastric adenocarcinoma. Methods: Between December 2013 and March 2018, robotic and laparoscopic radical gastrectomy performed in two centres were included. Both groups were compared with respect to perioperative short‐term outcomes. Results: Ninety‐four patients were included in the study. Anticoagulant and neoadjuvant chemotherapy use were higher in the robotic group ( p = 0.02, p = 0.02). There were conversions in the laparoscopy group whereas no conversions occurred in the robotic group ( p = 0.052). Operating time in the robotic group was longer ( p = 0.001). The number of harvested lymph nodes in the laparoscopic group was higher ( p = 0.047). Conclusion: Totally robotic technique with the da Vinci Xi ® robotic system provides similar short‐term results compared to laparoscopic surgery in radical gastrectomy.